Risk management foundations for a changing financial world - Haslett, Walter V. (CFA Institute investment perspectives series., 2010)
"Risk management has become virtually as important as portfolio construction and asset selection, more so after the financial crisis of 2008-2009. Those who understood the fine art of risk management survived the wreckage of the markets; those who depended entirely on risk modeling suffered greatly. The reality is that managing risk successfully is just as much art as science and involves a deep understanding of theory, market history, and meaningful risk measurement methodologies. For two decades, the CFA has been publishing some of the most important works on risk management from leading practitioners. This new volume outlines the evolution of risk management with key contributions from top risk managers including Rick Bookstaber, Peter Bernstein, Aswath Damodaran, Phillippe Jorion, Cliff Asness, Andrew Lo, among others. Covering the full range of risk management issues, the book includes key information on the history of firm and portfolio risk management, risk measurement, credit risk, and risk management of derivatives, pension funds, and international investments"--